Variation of bacterial communities in water and sediments during the decomposition of Microcystis biomass. - Dayong Zhao; Xinyi Cao; Rui Huang; Jin Zeng; Qinglong L Wu (PLoS ONE)
The bacterial community composition in water and sediment samples during the decomposition of Microcystis biomass were analyzed using the 454 pyrosequencing technique. We found dramatic shifts in the bacterial community composition of water and sediments after the addition of Microcystis biomass. Among all the detected phyla, only Firmicutes was found to be dominant in both water and sediment samples. The genus Clostridium sensu stricto was the absolutely dominant group in Firmicutes and showed drastic variations with incubation time during the decomposition process. Peak values in relative abundance of Clostridium sensu stricto appeared in the first few days for water and sediment samples. Environmental factors such as pH, dissolved oxygen (DO), and dissolved organic carbon (DOC) in water samples showed drastic variations during the decomposing process, which might be the prominent forces driving the variation of bacterial communities. The abundant genus, Clostridium sensu stricto, were thought to be well adapted to higher DOC and turbidity and lower pH and DO conditions. Compared with the sediment samples, the decomposition of Microcystis biomass had greater influence on the bacterial community composition in water and Clostridium sensu stricto might play important roles in the process of Microcystis biomass decomposition.